Development and Validation of the Career Competencies Indicator (CCI). (May 2013) - Francis-Smythe, Jan; Haase, Sandra; Thomas, Erica; Steele, Catherine
This article describes the development and validation of the Career Competencies Indicator (CCI); a 43-item measure to assess career competencies (CCs). Following an extensive literature review, a comprehensive item generation process involving consultation with subject matter experts, a pilot study and a factor analytic study on a large sample yielded a seven-factor structure; goal setting and career planning, self-knowledge, job performance, career-related skills, knowledge of (office) politics, career guidance and networking, and feedback seeking and self-presentation. Coefficient α reliabilities of the seven dimensions ranged from .93 to .81. Convergent validity was established by showing that all 7-CCs loaded substantially onto a single second-order factor representing the general CC construct. Discriminant validity was established by showing less than chance similarity between the 7-CCI subscales and the Big Five personality scales. The results also suggested criterion-related validity of the CCI, since CCs were found to jointly predict objective and subjective career success.